2009
DOI: 10.1111/j.1365-2672.2009.04320.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of Irish E. coli O157:H7 isolates of human, bovine, ovine and porcine origin

Abstract: Aims:  To determine the degree of relatedness between isolates of Escherichia coli O157:H7 of human, bovine, ovine and porcine origin. Methods and Results:  Escherichia coli O157:H7 isolates were compared using (i) PFGE XbaI patterns, (ii) PCR profiles of virulence genes and (iii) the DNA sequences of genes reported to play a role in pathogenicity. The 77 E. coli O157:H7 isolates demonstrated 49 different PFGE patterns of which, eight were common to multiple isolates, and the remaining 41 were distinct. Isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 47 publications
(105 reference statements)
2
15
0
Order By: Relevance
“…The panel of virulence genes in this study included 69 targets, and our results were in agreement with those of another study suggesting that increasing the number of virulence genes in the panel would increase the resolution of the virulence gene profiling (57). Various virulence gene profiles in swine STEC strains have also been reported elsewhere (38)(39)(40)(41)(42)(58)(59)(60). However, it was challenging to compare the results of this study with the results of those previous reports because all of the studies employed different panels of virulence genes.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The panel of virulence genes in this study included 69 targets, and our results were in agreement with those of another study suggesting that increasing the number of virulence genes in the panel would increase the resolution of the virulence gene profiling (57). Various virulence gene profiles in swine STEC strains have also been reported elsewhere (38)(39)(40)(41)(42)(58)(59)(60). However, it was challenging to compare the results of this study with the results of those previous reports because all of the studies employed different panels of virulence genes.…”
Section: Discussionsupporting
confidence: 81%
“…The degrees of genetic relatedness of swine STEC strains to strains from other animal species differed in those studies, and most studies focused on STEC O157:H7 (60,(69)(70)(71). Here, we found that STEC O59:H21 strains, which predominated in this swine population, were closely related among pigs in the same cohort.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…In a study carried out in Ireland, the prevalence of E. coli O157:H7 in pigs was found to be very low, and only four isolates were recovered from 1,710 pigs examined. However, three of these four contained the genes vtx2, eae, and hlyA, indicating their potential to cause illness in humans (68). While pork meat and products have generally not been implicated in human illness, in California in 2006, feral swine were implicated in contamination of agricultural fields and surface waterways with E. coli O157:H7, which caused a large outbreak linked to bagged spinach.…”
Section: Carriage Of Vtec In Pigsmentioning
confidence: 99%
“…Comparative studies in Ireland, Sweden and Japan revealed that cattle isolates possessing same phenotypic and genotypic traits as human clinical isolates have potential for causing human disease (Lenahan et al, 2009;Aspan and Eriksson, 2010;Lee et al, 2011). Kim et al (1999) suggested that E. coli O157:H7 strains isolated from diseased humans were members of a different lineage than strains typically isolated from healthy cattle.…”
Section: Introductionmentioning
confidence: 99%